Sexual and reproductive, empowerment, sexual rights, and sexual safe behaviors in mexican young people - Orozco-Gómez, Claudia; Jiménez Vázquez, Vicente; Amaro-Hinojosa, Marily Daniela; Valdez Montero, Carolina; Esparaza Dávila, Sandra Paloma (Horizonte Sanitario, 2024)
Objective: To determine the relationship between sexual and reproductive empowerment, knowledge of sexual rights and safe sexual behavior in young Mexicans. Materials and methods: The study was descriptive, correlational and cross-sectional. The sample consisted of 111 young people from Chihuahua, Mexico, who were selected at convenience. The information was collected through an online survey. Results: A significant difference in sexual and reproductive empowerment was found between men and women (p < 0.001), with men presenting higher scores (Mdn= 92.39) compared to women (Mdn= 79.34). No relationship was found between sexual and reproductive empowerment, knowledge about sexual rights and safe sexual behavior of these young people. Conclusion: The young people presented a high level of knowledge about sexual rights. In relation to sexual and reproductive empowerment, males presented higher scores than females. Safe sexual behavior was lower than in other studies in similar populations. In addition, no relationship was found between sexual and reproductive empowerment and knowledge of sexual rights and safe sexual behavior in this population, which emphasizes the need to continue studying these variables due to the scarcity of studies in this population. Key Words Empowerment; Reproductive Rights; Safe Sex; Young Adult.